2016
DOI: 10.1002/jbm.a.35698
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐responsive hydrogels from cellulose‐based polyelectrolytes and catanionic vesicles for biomedical application

Abstract: In this study, negatively charged catanionic vesicles/hydrophobically modified hydroxyethylcellulose polymers thermo-responsive hydrogels have been fabricated. Vesicular aggregates were found to act as multifunctional junctions for networking of modified-cellulose water solutions. The contributions of the electrostatic and hydrophobic interactions were evaluated by changing either vesicles composition or the polymer hydrophobic substitution. Thermal-induced size and lamellarity of hydrogel-enclosed vesicles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Protease activity of the holothurian complex was measured by the simple standard method using azocasein as a substrate [ 15 ]. The reaction mixture (300 μL) contained 3.3 mg/mL azocasein and 20 mM Tris-HCl (pH 7.5) or other buffers with pH in the range of 5.5 to 10.0 and 0.025 mg/mL protein complex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease activity of the holothurian complex was measured by the simple standard method using azocasein as a substrate [ 15 ]. The reaction mixture (300 μL) contained 3.3 mg/mL azocasein and 20 mM Tris-HCl (pH 7.5) or other buffers with pH in the range of 5.5 to 10.0 and 0.025 mg/mL protein complex.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the sea cucumber complex accumulates various elements, including those contained in very low concentrations in seawater. Some studies have shown that various metal ions can significantly affect the stability of complexes of very different nature, consisting of charged, hydrophobic and hydrophilic molecules [ 15 , 16 ], as well as proteins and nucleic acids [ 17 , 18 , 19 , 20 , 21 ]. The data indicate that metal-dependent interactions are formed, in addition to hydrogen bonds between the complex components [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, network meshes configure as a dynamic equilibrium, due to chains segments size and related Brownian motions, being the average mesh number and dimension constant [4,7]. Ordered zones formation is favored/hindered by environmental conditions such as temperature and ionic strength [8]. For instance, agarose undergoes a thermo-reversible gelation process occurring when hot solutions are cooled below~40°C.…”
Section: Hydrogels and Colloidal Structures For Drug Deliverymentioning
confidence: 99%
“…Drug delivery systems with adjustable properties have the ability to host a variety of molecules. For example, vesicularly cross-linked hydrogels are able to provide different environments for pharmaceuticals comprising bulk water, sites on polymeric chains, the interior of vesicles, and bilayers [14]. Most phthalocyanines are hydrophobic compounds that require association with other drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%